A Case of Recurrent Vulvar Carcinoma With Cardiac Metastasis: Case Report and Review of the Literature. (July 2020) - Linder, Revital; Lauterbach, Roy; Reiss, Arie
Abstract : A 67-yr-old female patient was diagnosed with squamous cell vulvar carcinoma and treated with a radical vulvectomy and bilateral sentinel lymphadenectomy. Three months after the surgery, the patient presented with local recurrence and underwent surgical excision of the mass, followed by chemotherapy. Eight months later, the patient was admitted due to weakness and pleural effusion. The patient underwent a chest computed tomography and echocardiogram, which revealed a large mass in the right ventricle penetrating into the pericardium and an additional mass residing on the tricuspid valve. She underwent a pericardial biopsy, and the pathology revealed a moderately differentiated squamous cell carcinoma metastasis. The patient was admitted thereafter in the oncological department for additional chemotherapy treatment. Because of a rapid deterioration in the patient's condition, only palliative treatment was given, and the patient died shortly after. Secondary cardiac tumors are very rare and have not been extensively studied in oncology. Therefore, optimal management is not entirely clear. It is extremely rare for vulvar cancer to metastasize to the heart, and only a handful of cases have been reported in the literature.